Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1756-3305-7-137
|View full text |Cite
|
Sign up to set email alerts
|

Dry season refugia for anopheline larvae and mapping of the seasonal distribution in mosquito larval habitats in Kandi, northeastern Benin

Abstract: BackgroundThe dynamics of mosquito populations depends on availability of suitable surface water for oviposition. It is well known that suitable management of mosquito larval habitats in the sub-Saharan countries, particularly during droughts, could help to suppress vector densities and malaria transmission. We conducted a field survey to investigate the spatial and seasonal distribution of mosquito larval habitats and identify drought-refugia for anopheline larvae.MethodsA GIS approach was used to identify, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Providing baseline information on the distribution and the abundance of the malaria vectors as well as their susceptibility to insecticides is very important for an effective malaria control in Togo. This study showed that in 2005, Anopheles larvae were present throughout the year in Lomé, but their frequency and abundance varied depending on the neighborhood and seasons as previously observed in other malaria endemic countries such as Benin (Govoetchan et al, 2014). The presence of larvae was not only related to rainfall because a high number of larvae was collected during the dry season.…”
Section: Discussionsupporting
confidence: 67%
“…Providing baseline information on the distribution and the abundance of the malaria vectors as well as their susceptibility to insecticides is very important for an effective malaria control in Togo. This study showed that in 2005, Anopheles larvae were present throughout the year in Lomé, but their frequency and abundance varied depending on the neighborhood and seasons as previously observed in other malaria endemic countries such as Benin (Govoetchan et al, 2014). The presence of larvae was not only related to rainfall because a high number of larvae was collected during the dry season.…”
Section: Discussionsupporting
confidence: 67%
“…calderoni , were associated with this type of larval habitat. Wells have been recognized as suitable larval habitats for mosquitoes, including as a refuge during the dry season for Anopheles , Aedes and Culex species [ 38 ], and treatment using larvivorous fish in wells has been associated with a reduction in malaria transmission [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precipitations occurring during the first round of tests do not seem to have affected the number of captured larvae. Relative air humidity [ 18 ] and the number of existing environmental breeding sites [ 19 ] have an influence on adult vector survival but did not result in differences in oviposition and hence container recolonization.…”
Section: Discussionmentioning
confidence: 99%